Effect of earthworms on mycorrhization, root morphology and biomass of silver fir seedlings inoculated with black summer truffle (Tuber aestivum Vittad.) - Tina Unuk Nahberger (Nature Portfolio, 2021)
Abstract Species of the genus Tuber have gained a lot of attention in recent decades due to their aromatic hypogenous fruitbodies, which can bring high prices on the market. The tendency in truffle production is to infect oak, hazel, beech, etc. in greenhouse conditions. We aimed to show whether silver fir (Abies alba Mill.) can be an appropriate host partner for commercial mycorrhization with truffles, and how earthworms in the inoculation substrate would affect the mycorrhization dynamics. Silver fir seedlings inoculated with Tuber. aestivum were analyzed for root system parameters and mycorrhization, how earthworms affect the bare root system, and if mycorrhization parameters change when earthworms are added to the inoculation substrate. Seedlings were analyzed 6 and 12 months after spore inoculation. Mycorrhization with or without earthworms revealed contrasting effects on fine root biomass and morphology of silver fir seedlings. Only a few of the assessed fine root parameters showed statistically significant response, namely higher fine root biomass and fine root tip density in inoculated seedlings without earthworms 6 months after inoculation, lower fine root tip density when earthworms were added, the specific root tip density increased in inoculated seedlings without earthworms 12 months after inoculation, and general negative effect of earthworm on branching density. Silver fir was confirmed as a suitable host partner for commercial mycorrhization with truffles, with 6% and 35% mycorrhization 6 months after inoculation and between 36% and 55% mycorrhization 12 months after inoculation. The effect of earthworms on mycorrhization of silver fir with Tuber aestivum was positive only after 6 months of mycorrhization, while this effect disappeared and turned insignificantly negative after 12 months due to the secondary effect of grazing on ectomycorrhizal root tips.